2018
DOI: 10.11113/jt.v81.12774
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical, Thermal and Durable Performance of Wastes Sawdust as Coarse Aggregate Replacement in Conventional Concrete

Abstract: Wood yields a number of by-products and Sawdust is as useful as others. Sawdust is regarded as a waste material and is effectively utilised as sawdust concrete in the construction of buildings. It is capable to be utilised as light-weight concrete and holds the quality of long duration heat transfer. In this study, three different ratios (1:1, 1:2 and 1:3) volume mix proportions of cement to sawdust were adopted to make sawdust concrete. At varied intervals of 7, 28 and 56 days of air curing, thermal and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…It is evident that, with the increasing content of sawdust and decreasing amount of river sand/crushed gravel, the UPV of the prepared concretes was decreased, which was ascribed to the increase in the sawdust-mediated porosity. The present findings agreed well with those of a previous study [47]. .…”
Section: Workability and Settingsupporting
confidence: 94%
See 1 more Smart Citation
“…It is evident that, with the increasing content of sawdust and decreasing amount of river sand/crushed gravel, the UPV of the prepared concretes was decreased, which was ascribed to the increase in the sawdust-mediated porosity. The present findings agreed well with those of a previous study [47]. .…”
Section: Workability and Settingsupporting
confidence: 94%
“…For a constant solution to binder ratio, the workability of the concretes was reduced with the increase in the sawdust amount as a substitute for river sand and crushed gravel. Several researchers [45][46][47] have obtained similar trends of results for the reduction in the workability of concrete containing lightweight aggregates. The limitations associated with the workability decrease in the concrete mixes due to the utilization of sawdust wastes as substitute for natural sand can be overcome by applying super-plasticizer.…”
Section: Environmental and Economic Benefitsmentioning
confidence: 60%
“…When cement, sawdust, and sand were combined in the following ratios: 1:1:1, 1:2:1, and 1:3:1 it was found that the 1:3:1 admixture had low thermal conductance compared to the other mix. Because there is more sawdust in the 1:3:1 mixture than in the other two, there is less heat transfer through that mixture [100,109].…”
Section: Thermal Properties Of Sawdust Compositementioning
confidence: 99%
“…In recent years, the use of industrial by-products, including sawdust, to produce LWCs has attracted many researchers. The thermal traits of sawdust-based concrete were investigated (Ahmed et al, 2018; Sosoi et al, 2022; Huseien et al, 2019). It was show that the inclusion of sawdust in the concrete matrix relatively reduces thermal conductivity by around 20% compared to OPC-based concrete.…”
Section: Introductionmentioning
confidence: 99%